1991
DOI: 10.1128/jb.173.2.929-932.1991
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of carbon-carbon bond cleavage of acetyl coenzyme A by using isotopic exchange catalyzed by the CO dehydrogenase complex from acetate-grown Methanosarcina thermophila

Abstract: The purified nickel-containing CO dehydrogenase complex isolated from methanogenic Methanosarcina thermophila grown on acetate is able to catalyze the exchange of [1-14C] acetyl-coenzyme A (CoA) (carbonyl group) with 12CO as well as the exchange of [3'-32P]CoA with acetyl-CoA. Kinetic parameters for the carbonyl exchange have been determined: Km (acetyl-CoA) = 200 ,uM, Vmax = 15 min-'. CoA is a potent inhibitor of this exchange (K1 = 25 ,uM) and is formed under the assay conditions because of a slow but detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 20 publications
(13 reference statements)
2
42
1
Order By: Relevance
“…After cleavage, the methyl group is transferred to the Co"+ atom of the Co/Fe-S component. The M. thermophila enzyme complex catalyzes an exchange of CoA with acetylCoA at rates fivefold greater than that of C. thermoaceticum acetyl-CoA synthase (46). The difference in rates may reflect the acetyl-CoA cleavage function for the M. thermophila enzyme, as opposed to the C. thermoaceticum enzyme which functions in the biosynthesis of acetyl-CoA.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…After cleavage, the methyl group is transferred to the Co"+ atom of the Co/Fe-S component. The M. thermophila enzyme complex catalyzes an exchange of CoA with acetylCoA at rates fivefold greater than that of C. thermoaceticum acetyl-CoA synthase (46). The difference in rates may reflect the acetyl-CoA cleavage function for the M. thermophila enzyme, as opposed to the C. thermoaceticum enzyme which functions in the biosynthesis of acetyl-CoA.…”
Section: Introductionmentioning
confidence: 92%
“…In M. thermophila, a COOH enzyme complex cleaves the C-C and C-S bonds of acetyl-CoA, as demonstrated by an exchange of CO with the carbonyl group of acetyl-CoA (46). The complex also oxidizes CO to CO2 and, therefore, is referred to as a CODH enzyme complex; however, the primary function is cleavage of acetyl-CoA during growth on *CH #COO- acetate.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6 for review). The acetyl-CoA/CoA exchange reaction of the Methanosarcina barkeri (1,7) and Methanosarcina thermophila (8) CODH/ACS complex also has been studied in great detail. The CO/acetyl-CoA exchange activity of the CODH/ACS complex also has been previously studied (8).…”
mentioning
confidence: 99%
“…It has been recently demonstrated that the CODH:corrinoid complex from Methanosarcina thermophila synthesizes acetyl-CoA from methyl iodide, CO and CoA [16,17]. Further, Raybuck et al [18] have shown that a similar complex from M. thermophila also catalyzes the acetyl-CoA-CO exchange as does CODH from Clostridium thermoaceticum. Our present findings clearly provide evidence for the existence of a functionally active complex of CODH and corrinoid in Clostridium thermoaceticum as in certain methanogens.…”
Section: Discussionmentioning
confidence: 99%